1998
DOI: 10.1159/000044922
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction Worsened by Superimposition of IgA Glomerulonephritis in a Patient with Overt Diabetic Nephropathy

Abstract: The combination of glomerulonephritis and diabetes nephropathy has been reported to occur in 1.8–22% of biopsy-proven diabetic nephropathy cases [1–6]. In these reports, however, the onset of glomerulonephritis during the course of diabetic nephropathy was not described in detail, and how the superimposition of glomerulonephritis affected renal function, particularly at the advanced stage of diabetic nephropathy. We recently encountered a patient, in whom the onset of IgA glomerulonephritis was detected clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…But a few reports have documented a rapid deterioration of renal function in patients with superimposed IgA nephropathy on top of DN, and diabetic microvascular complications are also worsened by superimposition of IgA nephropathy. 26,27 Because the inclusion criteria for renal biopsy in these retrospective series have included atypical clinical course like rapid loss of renal function among diabetic patients with renal involvement, selection bias leading to IgA nephropathy patients with aggressive renal outcome being picked up is a distinct possibility. It is apparent that only by prospectively recruiting type 2 diabetic patients with defined criteria for renal biopsy, although subsequently observing the clinical course of these patients, could one determine the true difference between the outcome of patients with DGS alone and those with superimposed IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…But a few reports have documented a rapid deterioration of renal function in patients with superimposed IgA nephropathy on top of DN, and diabetic microvascular complications are also worsened by superimposition of IgA nephropathy. 26,27 Because the inclusion criteria for renal biopsy in these retrospective series have included atypical clinical course like rapid loss of renal function among diabetic patients with renal involvement, selection bias leading to IgA nephropathy patients with aggressive renal outcome being picked up is a distinct possibility. It is apparent that only by prospectively recruiting type 2 diabetic patients with defined criteria for renal biopsy, although subsequently observing the clinical course of these patients, could one determine the true difference between the outcome of patients with DGS alone and those with superimposed IgA nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Glycation is also a suspected cause of decreased elimination of IgA by the liver and the protein accumulation in blood 83 . Serum IgA levels are significantly higher in diabetic patients than in healthy subjects 84 86 . High levels of IgA is a sign of diabetic nephropathy 86 , the most commonly recognized type of glomerular disease in the world and manifested by the formation of mesangial IgA deposits 87 .…”
Section: Discussionmentioning
confidence: 85%
“…Dear Sir, Kawasaki et al [1] recently reported that IgA nephropathy (IgAN) can aggravate the pace of progression towards renal insufficiency in patients with type 2 diabetes and proteinuria. It is now accepted that nondiabetic nephropathies sometimes superimposed upon diabetic glomerulosclerosis are much more frequent in non-insulin-dependent diabetes mellitus patients (NIDDM) than in insulin-dependent diabetes mellitus patients with proteinuria [2].…”
mentioning
confidence: 99%